Increasing teachers' use of behavior specific praise via Apple Watch prompting. Issue 3 (15th November 2021) - White, Kristi R.; Radley, Keith C.; Olmi, D. Joe; McKinley, Lauren E.
Abstract: This study evaluated the effects of a teacher prompting procedure to increase teacher behavior specific praise (BSP) using an Apple Watch. Participants included three Head Start general education teachers. An ABAB design across participants was used to examine the effects of Smart Watch‐based prompts on teachers' praise rate. The study consisted of four phases: (a) baseline, (b) teacher praise training and intervention, (c) withdrawal from intervention, and (d) reimplementation of intervention. Implementation of the intervention was associated with increases in both BSP and general praise for all participating teachers. Although averages did not meet the criterion set by the researcher of one statement per minute, these findings suggest a functional relation between implementation of the procedure and increases in teacher praise.